SOCIAL CAPITAL IN NON-BARTER TRANSACTION CHAIN IN PASAR BLANTE KAWANGKOAN, NORTH SULAWESI PROVINCE - Kimbal, Rahel Widiawati; Suman, Agus; Ashar, Khusnul; Manzilati, Asfi (Journal of Indonesian Economy and Business, 2012)
The research aims to find out the forms as well as the function of social capital in theÂ chain of economic activity in Pasar Blante (Blante market), one of the traditional markets inÂ Kawangkoan, North Sulawesi, particularly its non-barter transaction. This research employsÂ phenomenology-qualitative research method by involving triangulation as the method of dataÂ gathering. Spradley Model is chosen to analyze data. The results of the research highlight kindsÂ of social capital embodied in non-barter transaction in Pasar Blante which comprises trust,Â network, norms. These important factors are reflected in transaction chain involving many agentsÂ such as (1) the cattleâs owner; (2) maantung; (3) tukang blante; (4) cukong; and (5) the buyers.The contribution of social capital on non-barter transaction among people involving inÂ economic activity are embodied in (1) The transparent transaction resulting in lower informationcost among people taking part in that activity; (2) Free information access which enables them toÂ obtain credible information on getting qualified cattles with highly economical value; (3)Â Appreciation on someoneâs ownership shown in high-sense of belonging and responsibility ontaking care all cattles in Pasar Blante without additional charge; (4) Commitment on contactÂ agreement which minimizes the cancellation on transaction; (5) The transaction needs no writtenÂ document which legalizes the ownership of the buyer; (6) The availability of cattleâs food whichÂ in turn reduces the cattleâs food consumption cost; (7) Fast access on marketing which isÂ supported by all parties involving in the transaction as well as all elements of society. Moreover,Â this research elucidates that non-barter transaction also support other transactions such asÂ barter transaction and trade-in transaction. Finally, this non-barter transaction proves to beÂ contributive to increase the local revenues and generates the economic activity in the area.Keywords: social capital, traditional market, transaction, chain, non-barter.